Polyhedral oligomeric silsesquioxanes (POSSs): an important building block for organic optoelectronic materials. Issue 22 (26th May 2017) - Li, Zibiao; Kong, Junhua; Wang, FuKe; He, Chaobin
Abstract : Due to the unique hybrid structures and physical properties of polyhedral oligomeric silsesquioxanes (POSSs), hybridation with POSS has been demonstrated to be an important approach to build high-performance organic optoelectronic materials for applications in organic light-emitting diodes (OLEDs), liquid crystal display, sensors and electrochromic devices. Abstract : Due to the low-cost, facile processability and the capability of producing large areas of flexible thin films, organic optoelectronic materials have been considered among the most promising materials in the past two decades in both academic research and industry applications. Particularly, the incorporation of polyhedral oligomeric silsesquioxanes (POSSs) to develop high performance organic optoelectronic materials and the fabrication of these sophisticated materials into highly efficient devices are of significant interest because of the unique hybrid structures and physical properties of POSS. In this review, we present the recent advances in the development of POSS-based organic optoelectronic materials and devices, including organic light-emitting diodes (OLEDs), liquid crystal display, sensors and electrochromic devices. In addition, the insights into the uniqueness of POSS in microstructure, confined size effect, and their different organic substituents in the enhancement of the optoelectronic performance are illustrated. Finally, perspectives and challenges related to the further advancement of POSS-based organic optoelectronic materials are discussed, followed by the proposed design considerations to address the challenges that we will face in the future.